Different Chemical Forms of Calcium Supplementation in Perimenopausal Patients of Differentiated Thyroid Cancer with Normal Parathormone Levels - Jabin, Zeenat; Begum, Fatima; Ferdous, Jasmin; Islam, Urnas; Nahar, Nurun (Bangladesh Journal of Nuclear Medicine, 2019)
Abstract not available. Bangladesh J. Nuclear Med. 22(1): 58-60, Jan 2019